The The Analysis of Occupational Safety at The Recreational Sports Attractive of Pikatan Water Park, Temanggung Regency, Central Java, Indonesia - KURDIAWAN, LALANG -; Hanani, Endang Sri; Soenyoto, Tommy (Journal of Physical Education and Sports, 2021)
Occupational safety is very important, especially in recreational sports because the implementation of recreational sports has a high risk, as well as at the pikatan water park. The purpose of this study was to analyze occupational safety in the recreational sports attractive of Pikatan Water Park, in terms of human resources and infrastructure aspects. This type of research is qualitative. Respondents in this study were 2 managers, 2 employees, 3 operators and 28 visitors in two aspects of research, namely human resources aspects and infrastructure aspects. Data collection techniques used are observation, interviews, documentation, and document tracing. Data management for the results obtained using data collection, data reduction, data presentation, and drawing conclusions. The results of the study were for occupational safety in the recreational sport rides of Pikatan Water Park, Temanggung Regency, in terms of human resources, from 7 sub-aspects of the research, 6 sub-aspects were standardized. From the aspect of facilities and infrastructure, it was found that from 4 sub-aspects of the study there were 3 indicators in 3 sub-aspects that needed to be standardized. The Conclusion Research on occupational safety inrecreational sports water park has generally been met, but in terms of resources, it is necessary to meet employee performance appraisal standards. From the aspect of facilities and infrastructure, it is necessary to improve the physical condition of the rides and the need to fulfill the indicators for the prohibition of people with infectious diseases in the recreational area of the Pikatan Water Park.